Influence of climatic seasons in the presence of canine leptospirosis in northern and central Lima, Peru - Serrano-Martínez, Enrique (2020)
The aim of this study was to identify the behaviour of canine leptospirosis and its relationship with climatic seasons in the city of Lima, Peru. A retrospective study was designed analysing the results of canine sera that were evaluated with the micro-agglutination test (MAT) and its association with climatic data obtained from the National Meteorology and Hydrology System of Peru (SENAMHI) between 2014 and 2017. A generalized linear model was used to evaluate the association between positive cases to canine leptospirosis and the seasons, together with the adjustment of risk factors. The probability of presenting canine leptospirosis was higher in the spring-summer seasons compared to the autumn-winter season (p<0.05). Dogs diagnosed as positive were exposed to an air temperature of 20.6 °C and a relative humidity of 83.1%. Age, sex and place of origin showed no statistical association with the positive cases of Leptospira sp. It is concluded that the hottest seasons of the year (spring-summer) in the city of Lima are associated with canine leptospirosis.